2010
DOI: 10.1177/0022146510383495
|View full text |Cite
|
Sign up to set email alerts
|

The Social Construction of Illness: Key Insights and Policy Implications

Abstract: The social construction of illness is a major research perspective in medical sociology. This article traces the roots of this perspective and presents three overarching constructionist findings. First, some illnesses are particularly embedded with cultural meaning-which is not directly derived from the nature of the condition-that shapes how society responds to those afflicted and influences the experience of that illness. Second, all illnesses are socially constructed at the experiential level, based on how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
392
1
24

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 610 publications
(442 citation statements)
references
References 40 publications
(41 reference statements)
5
392
1
24
Order By: Relevance
“…The explanation of changing health practices receives support in medical sociology literature documenting the social and cultural bases of understandings of health (Conrad and Barker 2010). For example, studies have shown that among individuals with similar doctor diagnoses there are systematic differences in how symptoms are perceived and reported across ethnic groups (Zola 1966).…”
Section: Explanations For Health Assimilationmentioning
confidence: 99%
“…The explanation of changing health practices receives support in medical sociology literature documenting the social and cultural bases of understandings of health (Conrad and Barker 2010). For example, studies have shown that among individuals with similar doctor diagnoses there are systematic differences in how symptoms are perceived and reported across ethnic groups (Zola 1966).…”
Section: Explanations For Health Assimilationmentioning
confidence: 99%
“…Lay epidemiology fits within a social constructivist ontology which considers social phenomena—in this case illness—not as biological or natural ‘givens’ as in objectivist understandings of the social world, but as concepts that emerge from social interactions, which hold different meanings depending on the cultural and historical contexts in which they are produced and experienced 18, 19. For example, social constructivist approaches have critiqued ways in which obesity has been conceptualized as a ‘biological reality’ as opposed to a social phenomenon, and how this has been used to regulate and order people's bodies 20, 21.…”
Section: Introductionmentioning
confidence: 99%
“…However, this way of framing the relation still lacks a key protagonist of the organisation and provision of health care for the population. A negotiation model is strongly committed to a topic that has been central in the sociology of health: rescuing patients' (and sometimes, also professionals') perspectives in relation to illness (Conrad;Barker, 2010). This important task has had, however, an unexpected consequence: it has prompted an idea that the social dimension of health is exclusively a human affair, relinquishing the materiality of disease as a biomedical issue.…”
Section: The Lay-professional Relationshipmentioning
confidence: 99%